Investigation into Failure in Mining Wire Ropes—Effect of Crystallinity - Devasahayam, Sheila; Sahajwalla, Veena; Sng, Michael (Scientific Research, 2013)
A range of blends of polypropylene-polyethylene are investigated for their mechanical performances. These speciality polymer blends are chemically designed to suit high modulus/high load bearing mining wire rope applications subjected to continued bending and tensile stresses and fluctuating loads and are exposed to extreme weather conditions. In this paper we study the influence of different parameters on the performance of the wire ropes: chemistry of polymer, crystallinity of the polymer matrix, and the morphology. The FTIR and SEM studies revealed that the high fraction of polypropylene in polypropylene-polyethylene matrix lead to early failure as a result of incompatibility and phase segregation and high spherulite sizes of the polymer matrix.
Keywords: Mining Wire Ropes; Crystallinity; Polyolefin Blends; Morphology; FTIR; SEM